Microemulsion Loaded Hydrogel as an Advanced Approach for Topical Delivery of Drug: A Brief Review - Singh, Nitin; Singh, Charanjeet; Khare, Satyam; Patel, Preeti; Akram, Wasim; Joshi, Ramakant; Das Kurmi, Balak (Current Pharmaceutical Design, 2026)
Topical drug delivery has emerged as a promising alternative to conventional oral and parenteral routes, particularly for localized treatment and enhanced patient compliance. However, challenges such as poor drug solubility, low skin permeability, and instability of conventional formulations limit their effectiveness. To address these limitations, microemulsion-loaded hydrogels have gained significant attention as an advanced and efficient drug delivery system for topical applications. Microemulsions are thermodynamically stable, clear, isotropic mixtures of oil, water, surfactant, and co-surfactant that offer improved drug solubilization and skin penetration. When incorporated into hydrogels, they combine the penetration-enhancing properties of microemulsions with the viscosity and spreadability of hydrogels, resulting in a stable, non-greasy, and easily applicable formulation. This review highlights the fundamental characteristics of microemulsion-based hydrogels, including their composition and advantages over conventional topical systems. The synergistic effect of microemulsions and hydrogels enhances the drug loading capacity, prolongs drug release, and improves bioavailability, especially for hydrophobic and poorly permeable drugs. Furthermore, these systems minimize systemic side effects and improve patient adherence due to their non-invasive nature and ease of application. The review also discusses various examples of drugs successfully delivered through this platform, including antifungals, anti-inflammatories, and analgesics. Overall, microemulsion-loaded hydrogels represent a promising and innovative approach for effective topical drug delivery. With ongoing research and formulation advancements, they hold great potential for future clinical applications in dermatology and transdermal therapy.
Keywords: Microemulsion-based gel